2018
DOI: 10.3390/catal8100425
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrogenation, Hydrodeoxygenation, and Hydrocracking Processes of a Lignin Monomer Model Compound Eugenol over Magnetic Ru/C–Fe2O3 and Mechanistic Reaction Microkinetics

Abstract: Conversion of waste lignocellulosic (LC) biomass, a widely-available low-cost feedstock, into value-added biobased chemicals (and biofuels) has been gaining much attention recently. Therefore, the present lignin valorisation study was aimed at developing magnetically-separable highly-active catalysts for hydrodeoxygenation (HDO), also proposing surface chemical kinetics. Five carbonaceous substrate-deposited Ru were synthesised and tested for the HDO of monomer moiety eugenol. Their annealing temperatures diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The reaction using formic acid was performed in a batch reactor at 413 K. DDL yield and 6PP conversion obtained after 10 min of the reaction in all the solvent studied are presented in Table . 6PP hydrogenation at the reaction condition was expected to have negligible transport limitations, as observed in the hydrogenation studies of similar molecules in solvent over Ru and other transition metal catalysts. As evident from the table, the 6PP conversion was observed to be decreasing with the increasing dielectric constant of the solvent. For example, in methanol (ε = 32.7), the 6PP conversion was measured to be 14% (Table , entry 1), which was increased to 99% (Table , entry 5) in cyclohexane (ε = 2.0).…”
Section: Resultsmentioning
confidence: 77%
“…The reaction using formic acid was performed in a batch reactor at 413 K. DDL yield and 6PP conversion obtained after 10 min of the reaction in all the solvent studied are presented in Table . 6PP hydrogenation at the reaction condition was expected to have negligible transport limitations, as observed in the hydrogenation studies of similar molecules in solvent over Ru and other transition metal catalysts. As evident from the table, the 6PP conversion was observed to be decreasing with the increasing dielectric constant of the solvent. For example, in methanol (ε = 32.7), the 6PP conversion was measured to be 14% (Table , entry 1), which was increased to 99% (Table , entry 5) in cyclohexane (ε = 2.0).…”
Section: Resultsmentioning
confidence: 77%
“…The magnetic catalyst (Ru/C‐Fe 2 O 3 ) is reported for conversion of eugenol in hexadecane medium at 275 °C, 50 bat H 2 for 2 h. The Fe 2 O 3 treated at 600 °C (Ru/C−Fe 2 O 3 ‐600) showed high catalytic activity towards the formation of n ‐propylcyclohexane with 80 % yield (Table 3, entry 12). The annealing temperature of Fe 2 O 3 ‐600 composite resulted in high hydrodeoxygenation activity than 300, 500, and 750, which is because of better dispersion of Ru particles on Fe 2 O 3 ‐600 and is associated with high surface area (259 m 2 /g −1 ); the reported surface area of Fe 2 O 3 ‐300, Fe 2 O 3 ‐500, and Fe 2 O 3 ‐750 was 77, 209, 74 m 2 /g −1 [93] …”
Section: Catalytic Conversion Of Lignin‐based Compounds Into Cyclohexmentioning
confidence: 96%
“…Yousefi et al [ 27 ] found the analytical solution for the time-dependent stagnation point flow of a hybrid nano-fluid by considering a moving cylinder. Furthermore, the researchers presenting hybrid nano-fluid models can be seen in [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%